Analisis Tingkat Keterampilan Block Pada Permainan Bola Voli Peserta Ekstrakurikuler Di SMA Negeri 2 Kepahiang - Karim, Akbar Abdul; Asnawati, Asnawati; Martiani, Martiani (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
This study aims to determine the analysis of the level of block skills in volleyball games for extracurricular participants at SMA Negeri 2 Kepahiang. Where the research site is at SMA Negeri 2 Kepahiang. This type of research or research method is descriptive research. The research sample totalled 30 people. Data analysis of the data used in this study is descriptive analysis with percentages. Where the results of the block skills test in the volleyball game of extracurricular participants at SMA Negeri 2 Kepahiang in this study show the classification ‘very good’ to ‘very poor’. Then where the results of the final volleyball blocking skills test of 30 volleyball games of extracurricular participants at SMA Negeri 2 Kepahiang, as follows: A total of 3 people (10%) have a Very Poor Category. A total of 6 people (20%) have a category of less. A total of 14 people (47%) have a Fair Category and as many as 7 people (23%) have a Good Category. Based on the data above, it can be concluded that the block skill test in the volleyball game of extracurricular participants at SMA Negeri 2 Kepahiang is in the Fair category, namely as many as 14 Athletes or with a percentage of 47%. And there are suggestions with this research can improve the performance of volleyball coaches.